Hak-Hak Anak dalam Perspektif Islam - HM. Budiyanto (Raheema, 2014)
Children’s rights is, clearly or abstractly, something provided by their parents or guardians. Furthermore, the children’s rights means the responsibility of the parents or guardians. The United Nations appoints four basic rights for children, they are the rights of life, the rights of arising and evolving, the rights of protection, and the rights of participation. Moreover, how about Islam? This article will discuss the children’s rights in Islam, especially about the rights of arising and evolving, the rights of protection from purgatory, the rights of getting wealthy, the rights of education, the rights of justice, the rights of love, and the rights of play.